2004
DOI: 10.1111/j.1467-7660.2004.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

It is Possible to Just Give Money to the Poor

Abstract: Meghnad Desai of the London School of Economics recently suggested that, rather than 'giving fifty billion dollars of overseas aid', we should simply 'find the poor and give them one dollar a week . . . That would probably do more to relieve poverty than anything else'. Two experiences in Mozambique of simply handing out money show this is possible. Payments to demobilized soldiers over a two year period and single payments to flood victims were of the order of magnitude suggested by Desai. Rural people had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 4 publications
0
53
0
5
Order By: Relevance
“…It has also been found that poor and vulnerable families tend to be those that fail to fulfil the conditionalities needed to obtain the income transfer (Escobar and González de la Rocha, 2009), and that the conditionalities can create opportunities for corruption among those responsible for certifying them (de Brauw and Hoddinott, 2008). Moreover, there is no clear evidence of the effectiveness or efficiency of making social benefits conditional (Draibe and Riesco, 2009;Veras Soares, Ribas and Osorio, 2007;Veras Soares, Ribas and Hirata, 2008), owing to the difficulty of separating the effects of the conditionalities from those of the transfers (Hanlon, Barrientos and Hulme, 2010).…”
Section: Evaluation Of Conditionalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been found that poor and vulnerable families tend to be those that fail to fulfil the conditionalities needed to obtain the income transfer (Escobar and González de la Rocha, 2009), and that the conditionalities can create opportunities for corruption among those responsible for certifying them (de Brauw and Hoddinott, 2008). Moreover, there is no clear evidence of the effectiveness or efficiency of making social benefits conditional (Draibe and Riesco, 2009;Veras Soares, Ribas and Osorio, 2007;Veras Soares, Ribas and Hirata, 2008), owing to the difficulty of separating the effects of the conditionalities from those of the transfers (Hanlon, Barrientos and Hulme, 2010).…”
Section: Evaluation Of Conditionalitiesmentioning
confidence: 99%
“…However, there is no conclusive evidence of this, and some assessments of Bolsa Família even show the opposite effect, whereby the proportion of people seeking work is significantly higher in households using the programme (Camilo de Oliveira and others, 2007). The argument of the potential negative impact of conditional transfers on job seeking has been refuted by several authors (Alzúa, Cruces and Ripani, 2010;Hanlon, Barrientos and Hulme, 2010;Samson, 2009), who show the positive synergy between transfers and the employability of recipient families. In the study by Alzúa, Cruces and Ripani (2010), for Progresa in Mexico there was an increase of between 5% and 7% in the wage paid to male beneficiaries per hour of work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Good reviews on CCT programmes and their effects are now available, including Rawlings and Rubio (2003), Morley and Coady (2003), Rawlings (2005), Rawlings and Rubio (2005), Villatoro (2005), Cohen and Franco (2006), Reimers et al (2006), Lomelí (2008), Fiszbein andHanlon et al (2010 In my review of the literature I focus on educational effects, particularly on studies concerned with children's learning outcomes and progression in the education system.…”
Section: The International Research On Cct Programmesmentioning
confidence: 99%
“…Hanlon et al (2010) recognise four principles underpinning CCT programmes: (i) cash transfers as necessary for the fulfilment of the basic human right to a minimum income; (ii) governments as responsible for funding a non-contributory welfare programme able to reach the most destitute; (iii) commitment to long-term provision and large-scale coverage; and (iv) recognition of the productive capacity of the poor and its importance within a broad strategy for development. Common features are also underscored by several other authors, including Simões (2006), Valencia Lomelí (2008, and Barrientos & Santibáñez (2009).…”
Section: The Emergence Of Conditional Cash Transfer Programmes In Latmentioning
confidence: 99%